2016
DOI: 10.1097/sle.0000000000000242
|View full text |Cite
|
Sign up to set email alerts
|

Primary Closure Versus Biliary Drainage After Laparoscopic Choledocotomy

Abstract: With shorter durations of surgery and hospital stay, equivalent postoperative morbi-mortality, and an absence of the specific morbidity due to bile drainage, PC may be considered a safe and feasible option for the laparoscopic management of CBD stones by choledocotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(17 reference statements)
0
2
1
Order By: Relevance
“…The same result was reported in two recent studies [ 9 , 25 ]. In contrast, our result was inconsistent with some studies [ 4 , 13 , 14 , 17 , 48 ] that revealed that hospital stay was statistically significantly lower in the PDC group when compared with the TTD group. Moreover, a recent systematic review [ 11 ] and a comparative study [ 3 ] showed that hospital stay was statistically significantly longer in the TTD than in the PDC and ABS, but the two latter were no statistical difference.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The same result was reported in two recent studies [ 9 , 25 ]. In contrast, our result was inconsistent with some studies [ 4 , 13 , 14 , 17 , 48 ] that revealed that hospital stay was statistically significantly lower in the PDC group when compared with the TTD group. Moreover, a recent systematic review [ 11 ] and a comparative study [ 3 ] showed that hospital stay was statistically significantly longer in the TTD than in the PDC and ABS, but the two latter were no statistical difference.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, a recent systemic review [ 11 ] showed that the operative time was statistically significantly longer in the TTD group versus the PDC group and ABS group. Also, two meta-analyses [ 14 , 17 ] and a comparative study [ 48 ] showed that the operative time was statistically significantly longer in the TTD group than in the PDC group.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional biliary drainage has a long duration of catheterization, which reduces the quality of life of patients and brings trouble to home care. Especially in patients with poor nutritional status, there is the possibility of biliary peritonitis and septic shock caused by the shedding of the drainage tube [ 3 ]. There are also some postoperative complications in primary closure, the most common of which is postoperative bile leakage.…”
Section: Introductionmentioning
confidence: 99%